Improving Students’ Speaking Ability Through Picture Series: A Classroom Action Research at MTs Darul Ulum Budi Agung Medan - Syafitri, Rahayu; Maisaroh, Enni (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – The objective of this study was to boost the English-speaking proficiency of eighth-grade students at MTs Darul Ulum Budi Agung Medan by using picture series as visual teaching tools. Numerous students struggled with speaking due to insufficient self-assurance, restricted word knowledge, and a shortage of stimulating materials. The investigation examined whether picture series could help students achieve better fluency and precision when conveying procedural instructions.Method – The research employed Classroom Action Research (CAR) following the model by Kemmis and McTaggart, carried out over two cycles that included stages of planning, implementation, monitoring, and evaluation. A total of 35 students took part, with information gathered via initial tests, final assessments, classroom monitoring, and discussions. The evaluation of speaking skills encompassed aspects such as grammar, vocabulary, understanding, fluency, and pronunciation. Findings – The outcomes demonstrated a notable advancement in the students' speaking capabilities. The average score rose from 52.80 in the initial test to 71.31, and further to 78.40 and 79.20 in the subsequent assessments, reflecting a 50% increase in overall competence. Participants exhibited increased self-confidence, smoother delivery, and greater precision in articulating thoughts via sequenced images, with clear enhancements across all evaluated areas. Research Implications – These results highlight the importance of visual tools in promoting effective interaction and meaningful language production. In practical terms, the study provides educators with an effective approach to enrich speaking exercises in English as a Foreign Language (EFL) setting. Subsequent investigations might investigate the use of digital versions of image-based instruction and their effects on additional language abilities.